(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Tolosa Hunt syndrome is a rare disorder of uncertain aetiology characterized by severe periorbital headaches and recurrent painful unilateral opthalmoplegia. Resolution of findings on follow-up imaging and response to steroids is characteristic. This case is to emphasize the role of MRI in the diagnosis of this condition. J Bangladesh Coll Phys Surg 2023; 41: 234-236